The Integration of Cultural Content in English Textbook When English Rings a Bell for 7th Graders of Junior High School - Nurlaila Husain; Hilda Adrin; Sri Rumiyatiningsih Luwiti (TRANSBAHASA, 2022)
This research investigates the culture in the English textbook